Ethical Self-Reflection in Papers, Please. Issue 1 (10th December 2019) - Sarian, Antranig
This article argues that multiple endings and narrative memory within interactive narratives can engender ethical self-reflection in relationship with broader discourses surrounding controversial issues. It introduces the term 'expressed self' to describe this process. The expressed self is how an interactive text 'sees' the player – through either their alignment, faction favour, flags, etc – and is used to generate a personalised response to the player through their unlocked ending. This concept is then applied to a close analysis of Papers, Please by juxtaposing the 'Antegrian Husband and Wife' choice with the 'Snowier Pastures' ending. The manner in which this process takes place has implications for the ways in which videogames and interactive narratives engage with open literacy.